(untitled) (Journal Of Educational and Psychological Researches, 2025)
The current research aims to identify enlightened thinking among graduate students. It is limited to graduate students at Al-Anbar University for the academic year (2023-2024). 400 male and female graduate students in the scientific and humanities specializations were selected randomly from 15 colleges as the research sample. To achieve the objectives of the research, the researcher developed a scale to measure enlightened thinking, which consisted of 39 items based on the Schwartz model. The research concluded with the point that postgraduate students have enlightened thinking. In light of the research results, the researcher came out with several recommendations and suggestions.